Design, analysis and testing of a novel decoupled 2-DOF flexure-based micropositioning stage. (18th August 2017) - Yang, Shang; Chen, Weihai; Liu, Jingmeng; Chen, Wenjie
Abstract: This paper presents the design, analysis and testing of a novel decoupled 2-DOF flexure-based micropositioning stage driven by piezoelectric-actuators (PZTs). In order to enlarge the travel range, a Scott-Russell mechanism and leverage mechanism are arranged in series, constituting a two-grade displacement amplifier to conquer the small displacement of the PZT. The design micropositioning stage is composed of symmetrically distributed flexure modules and each flexure module comprises compound parallelogram flexure beams serving as input decoupling, which allows the output decoupling by employing the tridimensional double compound parallelogram flexure mechanism. Based on the analytical model of both the amplifier and the XY stage established in static and dynamic analysis, the dimensions and performance of the stage has been conducted, which are verified by finite element analysis with ANSYS Workbench and prototype experiment with the fabricated prototype of the designed stage. It can be seen that the workspace of the developed stage is 148.11   μ m × 149.73   μ m with the maximum output coupling errors of 0.693% and 0.637% in the y and x directions. The experimental results demonstrate that the proposed micropositioning stage possesses good performance in trajectory tracking and can achieve a wide range of precise positioning.